2013
DOI: 10.1002/mus.23696
|View full text |Cite
|
Sign up to set email alerts
|

Optical inhibition of motor nerve and muscle activity in vivo

Abstract: Introduction There is no therapeutic approach that provides precise and rapidly reversible inhibition of motor nerve and muscle activity for treatment of spastic hypertonia. Methods We used optogenetics to demonstrate precise and rapidly reversible light-mediated inhibition of motor nerve and muscle activity in vivo in transgenic Thy1::eNpHR2.0 mice. Results We found optical inhibition of motor nerve and muscle activity to be effective at all muscle force amplitudes and determined that muscle activity can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
0
38
2
Order By: Relevance
“…Optogenetics uses light-sensitive ion channels and pumps (typically from the microbial opsin gene family) to control neural activity with high temporal and spatial precision [1]. While optogenetics has been used to great effect in the brain [2], its application in the peripheral nervous system (PNS) has been limited to a few studies [3][7]. Previous work in our laboratory has described the first use of optogenetics to activate [4] and inhibit [7] motor neuron axons in anesthetized transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optogenetics uses light-sensitive ion channels and pumps (typically from the microbial opsin gene family) to control neural activity with high temporal and spatial precision [1]. While optogenetics has been used to great effect in the brain [2], its application in the peripheral nervous system (PNS) has been limited to a few studies [3][7]. Previous work in our laboratory has described the first use of optogenetics to activate [4] and inhibit [7] motor neuron axons in anesthetized transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…While optogenetics has been used to great effect in the brain [2], its application in the peripheral nervous system (PNS) has been limited to a few studies [3][7]. Previous work in our laboratory has described the first use of optogenetics to activate [4] and inhibit [7] motor neuron axons in anesthetized transgenic mice. These studies demonstrated the application of optogenetics in the PNS, but were limited by an inability to deliver opsins to target cell populations and deliver light for control of behavior in awake and freely moving animals.…”
Section: Introductionmentioning
confidence: 99%
“…This will include not just instrumentation advances such as higher magnetic field strengths, but also improved computational approaches for registration of brain anatomy across different individuals and new methods for interpreting with high confidence the nature of the signals seen, as with diffusion tractography. And for controlling human nervous systems, there has been recent engineering progress in the design and development of optogenetic interfaces that may be useful for bidirectional modulation of activity, such as for major peripheral nerves (Liske et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Initial approaches relied on illumination of the hindpaw in restrained animals [73] or the exposed sciatic nerve in anesthetized transgenic mice [90]. Illumination via fiber optic cables permitted basic reflexive assays of thermal and mechanical pain, but required simultaneous illumination of the hindpaw during stimulation [40,68,85] (Fig.…”
Section: Novel Approaches To Light Deliverymentioning
confidence: 99%